Estimating the climate change-driven global distribution of Fusarium proliferatum and mycotoxin risk assessment under future warming scenarios - Tagyan, Aya I.; AlAshaal, Sara; Alkhalifah, Dalal Hussien M.; Abdelghany, Walaa R.; Hozzein, Wael N. (Frontiers in Forests and Global Change, 2025)
IntroductionFusarium proliferatum is a globally distributed fungal pathogen of major agricultural significance, responsible for considerable crop losses and the production of hazardous mycotoxins that endanger food security and human health. Climate change is expected to modify the geographic distribution of plant pathogens, allowing their spread into previously unsuitable regions.MethodsThis study employed the Maximum Entropy (MaxEnt) species distribution modeling approach to evaluate the potential impacts of climate change on the global distribution of F. proliferatum under different Representative Concentration Pathway (RCP) emission scenarios. A total of 347 species occurrence records were obtained from the Global Biodiversity Information Facility (GBIF) and spatially filtered to minimize sampling bias. Bioclimatic variables, primarily temperature-related factors, were identified as key environmental determinants through systematic variable selection and correlation analysis. Model performance was evaluated using the Area Under the Curve (AUC) metric.ResultsThe MaxEnt model demonstrated excellent predictive accuracy (AUC = 0.844). Current distribution maps revealed high environmental suitability in tropical and subtropical regions, with moderate suitability in temperate zones. Future projections for 2050 and 2070 under both moderate (RCP 2.6) and severe (RCP 8.5) emission scenarios indicated notable poleward range expansion, particularly into northern Europe, northern Asia, and northern North America. The most substantial distributional shifts occurred under the severe emission scenario for 2070, showing extensive expansion of highly suitable environments into previously marginal regions. Temperature seasonality was identified as the most influential limiting factor globally.DiscussionThese findings suggest that ongoing climate change will substantially broaden the geographic range of F. proliferatum, heightening mycotoxin contamination risks in new agricultural areas and threatening food security in temperate zones historically unexposed to this pathogen. The study provides critical insights for developing proactive surveillance, biosecurity policies, and adaptive management strategies to mitigate the escalating risks posed by this economically important fungal pathogen under future climatic conditions.